The Effect of SAQ (Speed, Agility, And Quickness) Training on Developing The Efficiency of Certain Physical Indicators and Its Impact on The Level of Skill Performance, As Well As Its Influence on Some Functional Cardiac Variables In Basketball Players - Aladdin Abdullah Taha Abdullah Al-Muazani (Pubmedia Jurnal Pendidikan Olahraga, 2026)
Speed, Agility, and Quickness (SAQ) training is widely recognized as an effective approach to improve athletic performance in basketball, a sport requiring rapid movement, directional changes, and cardiovascular efficiency. Previous research has demonstrated that SAQ training significantly enhances speed, agility, and skill performance with statistically significant outcomes (p < 0.05) across multiple variables (Sun et al., 2025; Moselhy, 2020). Therefore, this study aimed to examine the effect of SAQ training on selected physical abilities, basketball skills, and functional heart variables, as well as to develop a tailored training program. An experimental one-group pretest–posttest design was used, involving 15 basketball players aged 17–18 years from Hit Sport Club. A preliminary study with 5 players was conducted to validate the procedures. Data were analyzed using paired sample t-tests. The results showed significant improvements (p < 0.05) in all variables. Physical performance increased, with transitional speed improving by 21.60% and agility by 24.06%. Skill performance also improved, including shooting accuracy (26.85%) and lay-up performance (41.86%). Functional heart variables demonstrated positive adaptations, including exercise heart rate (24.50%), resting heart rate (4.05%), and post-exercise heart rate (46.44%), consistent with previous findings (Lee et al., 2024; Si et al., 2025). In conclusion, SAQ training effectively enhances physical fitness, basketball skills, and cardiovascular efficiency, supporting its inclusion in modern basketball training programs.